Benign Pancreatic Neurofibroma with Malignant Imaging Features: A Case Report and Literature Review - Song, Ling; Jiang, Zhenpeng; Cui, Jian; Gao, BinYang; Luo, Yan (Frontiers in Surgery, 2022)
Pancreatic neurofibroma is a very rare benign neurogenic tumor unrelated to neurofibromatosis type 1 (NF-1). As the volume increases, it has the risk of malignant transformation. The surgical prognosis of pancreatic neurofibroma is good, but its preoperative imaging features are very similar to those of malignant tumors, which may affect the formulation of treatment plans. This article reports a case of giant neurofibroma of the pancreas with contrast-enhanced ultrasound (CEUS) as one of the diagnostic methods and discusses the tumor’s preoperative clinical features, laboratory examinations, and imaging features.